Implementasi Corporate Sacial Responsibility TP. Aneka Tambang Pada Pemberdayaan Masyarakat Tani (Suatu Studi di kecamatan Maba Kabupaten Halmahera Timur) - Maruga, Kits; Rorong, Arie Junus; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : The research objective is to mengetahuai how the process of implementation ofcorporate social responsibility in the community empowerment maba farmer in the district, thedistrict east halmahera sebagaiman mandated by law No. 40 of 2007. It was explained that theobligation CSR aims to create the company's relationship harmonious, balanced, and in accordancewith the environment, values, norms, and local culture. To know the process of implementingcorporate social reponsibility on a farm community prmberdayaan the research method used isqualitative method, which is where the researcher as a key instrument.In peleksanaan corporate social responsibility program of PT. Antam to the empowerment ofthe farmers. Antam start with a Base line data, which prepares the program what to do, then analyzethe data suda collected in order to determine the level of success to be achieved, and so do the designprogram, and at the implementation stage of society tanilah are active in a given program and themonitoring and efaluasi of Antam parties it is intended that the program carried obtain maximumresults. so far CSR program on farmers suda so we feel and suda goes well, ranging fromunderstanding the challenge of agriculture, pelatiahan-training and the provision of land, for thepeople who do not have agricultural land and the provision of means of transportation to rejuvenate usgo into the garden or agricultural land ,In peleksanaan corporate social responsibility program of PT. Antam's farmer communityempowerment suda well underway, and has been doing so, in accordance with company policy so thatprograms adapted to the conditions of human resources and natural resources in the region, so thatthe programs can be maintained sustainability. So the future of corporate social responsibility better inrealizing the company's policy and is mandated by law.Keywords: Implementation of Corporate Social Responsibility Pt. Antam on Community Empowerment ofFarmers in Sub Maba East Halmahera